The Intra-Americas Sea Low-level Jet - Amador Astúa, Jorge Alberto (2008)
A relevant climate feature of the Intra‐Americas Sea (IAS) is the low‐level jet (IALLJ) dominating the IAS circulation, both in summer and winter; and yet it is practically unknown with regard to its nature, structure, interactions with mid‐latitude and tropical phenomena, and its role in regional weather and climate. This paper updates IALLJ current knowledge and its contribution to IAS circulation–precipitation patterns and presents recent findings about the IALLJ based on first in situ observations during Phase 3 of the Experimento Climático en las Albercas de Agua Cálida (ECAC), an international field campaign to study IALLJ dynamics during July 2001. Nonhydrostatic fifth‐generation Pennsylvania State University National Center for Atmospheric Research Mesoscale Model (MM5) simulations were compared with observations and reanalysis. Large‐scale circulation patterns of the IALLJ northern hemisphere summer and winter components suggest that trades, and so the IALLJ, are responding to land–ocean thermal contrasts during the summer season of each continent. The IALLJ is a natural component of the American monsoons as a result of the continent's approximate north–south land distribution. During warm (cold) El Niño–Southern Oscillation phases, winds associated with the IALLJ core (IALLJC) are stronger (weaker) than normal, so precipitation anomalies are positive (negative) in the western Caribbean near Central America and negative (positive) in the central IAS. During the ECAC Phase 3, strong surface winds associated with the IALLJ induced upwelling, cooling down the sea surface temperature by 1–2 °C. The atmospheric mixed layer height reached 1 km near the surface wind maximum below the IALLJC. Observations indicate that primary water vapor advection takes place in a shallow layer between the IALLJC and the ocean surface. Latent heat flux peaked below the IALLJC. Neither the reanalysis nor MM5 captured the observed thermodynamic and kinematic IALLJ structure. So far, IALLJ knowledge is based on either dynamically initialized data or simulations of global (regional) models, which implies that a more systematic and scientific approach is needed to improve it. The Intra‐Americas Study of Climate Processes is a great regional opportunity to address trough field work, modeling, and process studies, many of the IALLJ unknown features.